PERKEMBANGAN KOPERASI PETANI SAWIT (KPS) PERINTIS PERUSAHAAN INTI RAKYAT PERKEBUNAN (PIR BUN) OPHIR JAMBAK KAB.PASAMAN BARAT (1991-2011) - susanti, Eka; Ansofino, Ansofino; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRACT West Pasaman a palm oil producing region that is dominant in western Sumatra, in fact the result of oil palm does not make social conditions well aswith such circumstances, some palm oil growers do not make the condition better as a society. With such circumstances some peasant farmers inspiration to improve socio-economic conditions of farmers by establishing cooperative KPS named PIR - BUN ophir pioneering cooperative aims to improve the way sales of palm oil produced by farmers to increase welfare of smallholders who are in KanagarianLingkuangAuaPasaman west Pasaman district. The purpose of this study is to describe the background of the establishment of cooperative smallholders (PPP) pioneer, farmer cooperative businesses palm (PPP) pioneer, describes socioeconomic smallholders after the establishment of farmer cooperatives palm (PPP) company pioneering nucleus estates (PIR BUN)ophir tuft kec.Pasaman district.Pasaman west of the years 1991 to 2011.The method used in this paper is the historical method with the following steps : heuristic (collection of sources that need to be in writing), source criticism, and interpret facts, and set forth in writing the history of the so-called scientific historiography. Businesses PPP pioneer covers several business units, namely; weserda, savings and loans, transportation, services and other revenue in the form of bank fees, KJUB services, fees cooperation, Adm. power, Adm. new members, and Flowers Bank.Based on the research that has been done can be concluded that, pioneering PPP Pir Bun OphirKab.PasamanJambak West has been able to bring changes to the social conditions of smallholders and socio-economic conditions of smallholders better than before the cooperative. Keyword : Farmer Cooperative Palm